# How do you solve #log_[2] (x+20) - log_[2] (x+2) = log_[2] x#?

##### 2 Answers

#### Explanation:

First of all, let's establish the domain. As any logarithmic expression can only have positive arguments, the following conditions must hold:

- In order for the first logarithmic expression to be defined,
#x + 20 > 0 " "<=>" " x > -20# must hold. - For the second logarithmic expression,
#x + 2 > 0 <=> x > -2# must hold. - For the third logarithmus,
#x > 0# must hold.

As

==========

Now, let's solve the equation.

First of all, we can use the logarithmic law

#log_a (m) - log_a(n) = log_a (m/n)#

In this case, we get:

#log_2(x+20) - log_2(x+2) = log_2(x)#

#<=> log_2 ((x+20)/(x+2)) = log_2(x)#

Now that on both sides we have just one logarithmic expression, we can use

#<=> (x+20)/(x+2) = x#

... multiply both sides with

#<=> x + 20 = x(x+2)#

#<=> x^2 + x -20 = 0#

The solutions for this quadratic equation are

However, as we have established that

Thus, our only solution is

I found

#### Explanation:

Try this: